التوافق النفسي وعلاقته بالدافعية للتعلم لدى تلاميذ السنة الرابعة متوسط - لغريب حسيبة; عبد اللاوي خديجة (University Of Eloued جامعة الوادي, 2024)
ملخص الدّراسة بالعربية هدفت دراستنا إلى الكشف عن طبيعة العلاقة التّي تربط التوافق النّفسي بالدّافعية للتّعلم لدى تلاميذ السنة الرابعة متوسط ، حيث تمت صياغة الإشكالية العامة على النحو التّالي : " هل توجد علاقة ارتباطية بين التوافق النّفسي والدّافعية للتّعلم لدى تلاميذ الرّابعة متوسط ؟ " وقد شملت عينة الدّراسة على 100 تلميذ وتلميذة من تلاميذ السنة الرابعة متوسط بمتوسطة بوغزالة محمد الصالح ببلدية اميه ونسة بالوادي ، وتم تطبيق مقياس التوافق النّفسي لـزينب شقير ، ومقياس الدّافعية للتّعلم ليوسف قطامي ، وقد تم الاعتماد على المنهج الوصفي ، وقمنا بتطبيق معامل الارتباط بيرسون لمعالجة البيانات والحصول على النتائج ، وقد أسفرت النتائج عن ما يلي: - توجد علاقة ارتباطية دالة عند مستوى دلالة 0.01 ، بين التوافق النفسي والدافعية للتعلم لدى تلاميذ الرّابعة متوسط. - توجد علاقة ارتباطية دالة عند مستوى دلالة 0.01 ، بين التوافق الشّخصي الانفعالي والدافعية للتعلم لدى تلاميذ الرّابعة متوسط. - توجد علاقة ارتباطية دالة عند مستوى دلالة 0.01 ، بين التوافق الصّحي والدافعية للتعلم لدى تلاميذ الرّابعة متوسط. - توجد علاقة ارتباطية دالة عند مستوى دلالة 0.01 ، بين التوافق الأسري والدافعية للتعلم لدى تلاميذ الرّابعة متوسط. - توجد علاقة ارتباطية دالة عند مستوى دلالة 0.01 ، بين التوافق الاجتماعي والدافعية للتعلم لدى تلاميذ الرّابعة متوسط. Summary of the study in English Our study aimed to reveal the nature of the relationship that links psychological adjustment to the motivation to learn among fourth-year intermediate students, where the general problem was formulated as follows: “Is there a correlation between psychological adjustment and motivation to learn among fourth-year intermediate students?” “The sample of the study included 100 male and female students from the fourth year of middle school at BouGhazala Muhammad Al-Saleh Middle School in the municipality of UmyhOunsa in El oued. The psychological adjustment scale by ZainebChoukair and the motivation to learn scale by Youssef Qatami were applied. The descriptive approach was relied upon, and we applied the Pearson Correlation coefficient to treat Data and obtaining results. The results resulted in the following: There is a significant correlation, at a significance level of 0.01, between psychological adjustment and motivation to learn among fourth-year middle school students. There is a significant correlation, at a significance level of 0.01, between personal emotional adjustment and motivation to learn among fourth-year middle school students. There is a significant correlation, at a significance level of 0.01, between healthy adjustment and motivation to learn among fourth-year middle school students. There is a significant correlation at the significance level of 0.01, between family harmony and motivation to learn among fourth-year middle school students. There is a significant correlation at the significance level of 0.01, between social adjustment and motivation to learn among fourth-year middle school students.
دراسة ميدانية بمتوسطة بوغزالة محمد الصالح ببلدية "اميه ونسة" بالوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التوافق النفسي; Compatibilité psychologique; Psychological compatibility; Motivation to learn; الدافعية للتعلم; Motivation à apprendre